Effects of DSP Integration Besides Arm Structures on Video Decoding - Ilhan, Hamza Osman; Akbas, Ahmet (TURGUT OZAL UNIV, 2012)
Today, the ARM processor architecture is used in many electronic devices as the central processing unit. Studies in this field have rapidly progressed because of using ARM architecture in indispensable devices in our daily life such as mobile phones, media players and audio systems. At the same time, users' expectations in this processor are increasing every day. Recently, ARM processors cannot meet these expectations of users alone. At this point, embedded system designers are using engaged DSP processors. They started to produce chips whose popularity is getting higher day after day with the name as System on Chip (SoC) containing ARM and DSP cores together. In this study, an OMAP series chip has been researched. Benefits of using DSP alongside ARM processor are stated during encoding video data in several formats.
Keywords: ARM; DSP; codecs; OMAP; Pandaboard; Computer Science; Engineering; Telecommunications